International Conference on Climate Risk Management, inputs for the Intergovernmental Panel on Climate Change's Sixth Assessment Report. (14th September 2019) - Singh, Roop K.; Arrighi, Julie; Coughlan de Perez, Erin; Warrick, Olivia; Suarez, Pablo; Koelle, Bettina; Jjemba, Eddie; van Aalst, Maarten K.; Roberts, Debra C.; Pörtner, Hans O.; Jones, Richard G.
ABSTRACT: In April 2017, over 70 scientists, policymakers and practitioners from 32 countries convened at the International Conference on Climate Risk Management in Nairobi, Kenya. This conference utilized innovative approaches to facilitate a process of constructive, critical reflection of the existing climate risk management knowledge base, as well as its relevance to decision-maker needs and views of the most vulnerable people. The conference articulated recommendations to the Intergovernmental Panel on Climate Change (IPCC) in the development of their Sixth Assessment Report (AR6) – in support of the Chair's vision for AR6 to have a strong focus on solutions. This report highlights key recommendations distilled from these discussions in areas such as risk-framing approaches and risk metrics. The meeting also suggested that the next IPCC assessment could be strengthened by stronger interaction with practitioners and policymakers working at the forefront of implementing global climate and development agreements, especially in the most vulnerable contexts, and identified associated research priorities.